ANALISIS TINGKAT EMISI CO2 DARI PENGGUNAAN BAHAN BAKAR FOSIL DI KOTA PEKANBARU UNTUK PENGEMBANGAN MODUL KONSEP ISU LINGKUNGAN PADA MATA KULIAH PENDIDIKAN LINGKUNGAN - Syafrizal Ulum; Sri Wulandari; Suwondo ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was conducted to determine the level of CO2 emissionsfrom fossil fuel use in Pekanbaru city and develop module concept of environmentalissues in the subject of environmental education. The study was conducted in November2012 to May 2016. The method used in this study is a documentation method to collectdata on the various agencies related to research, whereas the module development isdone using ADDIE models at analysis, design, and development. Parameters usedinclude emission sources and CO2 emission levels, vegetation trees in the green belt, aswell as climatic conditions. Sources of emissions come from the use of fuel oil (BBM),electricity and LPG (Liquid Petroleum Gas). The highest emission levels derived fromfuel, which reached 192.636 Gg CO2. Tree vegetation in the Green Line Pekanbaru Cityhas 49 species and 11 588 individuals and that most are Swietenia macrophylla withabsorptive capacity of 295.73 kg CO2 / tree / year. Climatic conditions in Pekanbarucity is Fluctuating. The observed climate parameters such as temperature, humidity andrainfall results can be developed into a module by showing a very valid category (4.2)and the test results are limited by learners show very good category (90.6).Keywords: CO2 Emissions, Fossil Fuels, green line of vegetation, climate, module